2017
DOI: 10.1186/s13063-017-2091-4
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of an educational intervention for sodium restriction in patients with hypertension: study protocol for a randomized controlled trial

Abstract: BackgroundThe effectiveness of nonpharmacological interventions in blood pressure reduction has been evidenced by several studies. Nevertheless, as adherence to a low-sodium diet is poor, interventions regarding habit changing should be of a motivational nature in order to develop the ability of overcoming obstacles regarding sodium-restriction behavior.The present study aims to describe the protocol and randomization of a clinical trial design in order to evaluate the effectiveness of an educational intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…After a 6-week intervention, the results of a study [25] conducted on patients with heart failure showed an improvement in attitude subscale scores, which suggests a positive shift in their attitudes toward adhering to a low-sodium diet. Our findings agree with other studies regarding participants perceiving fewer barriers to sodium restriction, improving the ability to read labels, choose foods and eat meals, and reinforcing the perceived ability to deal with possible obstacles [26,27]. Participants presented positive attitudes toward following a low-sodium diet.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…After a 6-week intervention, the results of a study [25] conducted on patients with heart failure showed an improvement in attitude subscale scores, which suggests a positive shift in their attitudes toward adhering to a low-sodium diet. Our findings agree with other studies regarding participants perceiving fewer barriers to sodium restriction, improving the ability to read labels, choose foods and eat meals, and reinforcing the perceived ability to deal with possible obstacles [26,27]. Participants presented positive attitudes toward following a low-sodium diet.…”
Section: Discussionsupporting
confidence: 90%
“…Prior to enrollment, participants provided informed consent, and the study protocol (protocol number 150496) was approved by the hospital's institutional review board. Additionally, the study protocol has been registered at ClinicalTrials.gov (NCT02848690) and published [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] evaluated the effects of nutrition education on decreasing sodium intake and increasing potassium intake in prehypertensive or untreated hypertensive Korean patients and found that education was effective in reducing sodium intake but not in increasing potassium. A recent meta-analysis also reported that global mean potassium intake (2.25 g/day) falls below the recommended intake level of >3.5 g/day, with the lowest mean potassium intake reported in Asia (1.89 g/day) and the highest mean intake in Eastern and Western Europe (3.53 g/day and 3.29 g/day, respectively) [31]. These findings, together with ours, indicate the importance of raising awareness about high potassium intake to effectively lower BP, especially in Asia.…”
Section: Discussionmentioning
confidence: 99%